Energy poverty policies: reviewing the policy design - Guyet, Rachel (2019)
Energy poverty is a complex, multidimensional and context-based challenge. Thus, policy approaches need to be comprehensive and coherent with the other public policies. To achieve this, multidisciplinary and multi-stakeholder bodies, dedicated to designing energy poverty policies and measures, should be established at the national and local levels in particular. In parallel, the adverse impacts of various other policies (fiscal, labour, climate, housing, energy, etc.) on energy poverty need to be assessed and steps taken to minimize or eliminate them. Critically, energy poverty policies must be designed through participatory processes, involving the people affected.